Integrated Meta-omics Reveals a Fungus-Associated Bacteriome and Distinct Functional Pathways in Clostridioides difficile Infection - David B. Stewart (American Society for Microbiology, 2019)
ABSTRACT There has been no prior application of matched metagenomics and metatranscriptomics in Clostridioides difficile infection (CDI) evaluating the role of fungi in CDI or identifying community functions that contribute to the development of this disease. We collected diarrheal stools from 49 inpatients (18 of whom tested positive for CDI) under stringent inclusion criteria. We utilized a tiered sequencing approach to identify enriched bacterial and fungal taxa, using 16S and internal transcribed spacer (ITS) rRNA gene amplicon sequencing, with matched metagenomics and metatranscriptomics performed on a subset of the population. Distinct bacterial and fungal compositions distinguished CDI-positive and -negative patients, with the greatest differentiation between the cohorts observed based on bacterial metatranscriptomics. Bipartite network analyses demonstrated that Aspergillus and Penicillium taxa shared a strong positive relationship in CDI patients and together formed negative cooccurring relationships with several bacterial taxa, including the Oscillospira, Comamonadaceae, Microbacteriaceae, and Cytophagaceae. Metatranscriptomics revealed enriched pathways in CDI patients associated with biofilm production primarily driven by Escherichia coli and Pseudomonas, quorum-sensing proteins, and two-component systems related to functions such as osmotic regulation, linoleic acid metabolism, and flagellar assembly. Differential expression of functional pathways unveiled a mechanism by which the causal dysbiosis of CDI may self-perpetuate, potentially contributing to treatment failures. We propose that CDI has a distinct fungus-associated bacteriome, and this first description of metatranscriptomics in human subjects with CDI demonstrates that inflammation, osmotic changes, and biofilm production are key elements of CDI pathophysiology. IMPORTANCE Our data suggest a potential role for fungi in the most common nosocomial bacterial infection in the United States, introducing the concept of a transkingdom interaction between bacteria and fungi in this disease. We also provide the first direct measure of microbial community function in Clostridioides difficile infection using patient-derived tissue samples, revealing antibiotic-independent mechanisms by which C. difficile infection may resist a return to a healthy gut microbiome.